Investigation of Grewia mollis Gum as Biopolymer Drag Reducing Agent - ADAMU, Yahaya Yakubu; ADAMU, Mohammed Bello; ABDULSALAM, Surajudeen; MILTON, Roy Zwalatha; MUHAMMAD, Muhammad Aminu (ABUAD Journal of Engineering and Applied Sciences, 2024)
The hydraulic fracturing treatment relies heavy on fracturing fluid. Finding inexpensive polymer that lowers the pressure gradient in turbulent flow systems during hydraulic fracturing is crucial for the development of shale gas. Most researches focused on investigating the effects of polymers such as partially hydrolysed polyacrylamide, polyethylene oxide, guar gum, xanthan gum and synergies of mixtures as friction reducing polymers. The use of Grewia Mollis mucilage as the natural polymer as a potential friction reducer in slickwater fracturing treatment was the main focus of this study. The sample of Grewia gum was obtained and the mucilage was extracted from the inner stem bark by maceration in water at ambient temperature. The mucilage was the oven-dried at a temperature of 50 oC. Atomic Absorption spectrophotometer (AAS) and Fourier Transform Infrared (FT-IR) were employed to identify the elemental composition and the functional groups of the plant. The FT-IR spectrum exhibited typical peaks and bands characteristics of polysaccharide, while the ASS result shows the presence of minute quantity (0.219 mg/100 g) of lead (Pb) in the plant may show contamination (toxicity). The rheological measurements of the mucilage plotted on the shear viscosity graph exhibit shear-thinning or pseudo-plastic behaviour. Formulated slickwater fracturing fluid at various concentrations ranging from 200 to 500 ppm, were run in a constructed closed flow loop of 0.01905 m diameter of galvanised steel pipe, test section length of 2 m and entrance length of 2 m. Drag reduction was measured at flow rates (2.3, 2.8, 3.2, 3.6 and 4.0) m3/hour at different concentrations (200 to 500) ppm. Percentage friction reduction of 37% was achieved at Reynolds number of 74269 by addition of 200 ppm of the fluid while 56% was achieved at Reynolds number 74269 by addition of 500 ppm. This indicates that Grewia mollis mucilage exhibit drag reducing potential and can be applied in slickwater hydraulic fracturing application.